What is the optimal composition of an athlete's diet? - Broad, E. M.; Cox, G. R. (European Journal of Sport Science, 2008)
Designing the most suitable diet for an athlete requires an intimate knowledge of the relevant scientific literature, the training and competition demands of the sport, the individual athlete's preferences and social situation. The scientific literature contains an abundance of information on nutritional demands of athletes undertaking endurance or strength training programmes, but much less information is available on sprint/power sports, team, racquet, weight-making, aesthetic (diving, gymnastics), and skill-based events. Furthermore, most research has been undertaken on adult males, with the assumption that females and adolescent athletes follow the same patterns of fuel usage and requirements. Consequently, assessing the optimal composition of an athlete's diet relies at best on an informed interpretation of the scientific data, plus individually collected observations. The aims of this article are to provide an overview of the current evidence on macronutrient requirements for day-to-day training for a range of different athletes, provide some recommendations regarding formulating an athlete's diet, and highlight areas where more research is required.